The Effectiveness of Game Based Learning “Board Race Game” to Fostering Vocabulary Mastery - Fauziyah, Lailatul (Universitas Muhammadiyah Gresik, 2024)
Vocabulary is a basic component of language. Before learning English, students need to understand some components of the language, such as vocabulary. however, there are many students who have low vocabulary mastery with almost the same factors for each student. Therefore, the researcher conducted a study using the game method in a language teaching as an effort to increase students' ability in vocabulary mastery. in this study the researcher used grade 10 MA Muhammadiyah Banyutengah students as many as 21 students. In collecting data, the researcher conducted 5 meetings in the study, 1 pre-test, 3 treatments, and 1 post-test. It can be seen from the pre-test score is 43.62 and the posttest is 73.86 where the difference between the two tests is 30.44. After implementing the treatment, the researcher can solve the problem in improving students' vocabulary mastery. From this research it can be concluded that the use of the board racing game method is very effective in improving students' ability to master English vocabulary in class X MA Muhammadiyah 02 Banyutengah.